Tracheostomy care for ICU survivor - Jamaludin, Thandar Soe Sumaiyah (2018)
Tracheotomy is a common procedure in patients who are suffering from obstruction of upper airways and to assist weaning from ventilatory support in patients in intensive care units. Nurses must provide proper care to tracheostomy patients to prevent complications. One of the most important considerations is effective mobilization of secretions, and a suction catheter is the most important tool for that purpose.